Growing Consumer Awareness and CSR, in context of Green Marketing as a way forward for India. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The concept of Green marketing has subconsciously become entwined into various aspects of the society. Presently there are a significant number of businesses which have grown to become extremely conscious about using/selling products that are said to be non-eco-friendly and environmentally unsafe. Customers are willing to spend extra for products that observe eco-friendly standards. CSR (Corporate Social Responsibility) index has become the new normal with businesses adopting models which echo greening, by producing/buying Green products for the welfare of the environment and society. This paper mainly merges with how the execution of Green marketing can be a road to promote CSR